Socio-demographic characteristics and career choices amongst Chilean dental students. - Karla Gambetta; Rodrigo Mariño; Mike Morgan (Universidad de Concepción., 2014)
This cross-sectional study aimed to explore the socio-demographic and career choice characteristics of dental students in two publicly funded universities in Chile. A total of 601 dental students participated in the study with a 53% response rate.The written survey covered age, gender, type of school attended, place of residence, parental occupation, level of education, tuition fees payment methods, along with motivations and preferences towards dentistry as a career. The respondents had an average age of 22 years old. Sixty one percent of respondents were female, and the majority had completed secondary education in private and subsidized schools with only 21.5% having finished in public schools. Most of the students covered their tuition fees with parental money (37.1%), followed by any type of loan (27.9%). The majority of students (63.8%) had placed dentistry as their first career choice with self-motivation being the most important reason for their decision. This study provides a description of the socio-demographic and economic profile of Chilean dental students and provides insights about career decision issues. It also purposes areas for further research and management by academics for future program development.